2015
DOI: 10.1007/s11123-015-0455-x
|View full text |Cite
|
Sign up to set email alerts
|

Innovation spillovers and firm performance: micro evidence from Spain (2004–2009)

Abstract: This article analyses the impact that R&D expenditures and intra-and inter-industry externalities have on the performance of Spanish firms. Despite the extensive literature studying the relationship between innovation and productivity, there are far fewer studies in this particular area examining the importance of sectoral externalities, especially focused on Spain. One novelty of this study, conducted for the industrial and service sectors, is that we also consider the technology level of the sector in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 60 publications
1
14
0
10
Order By: Relevance
“…In this regard, several studies have provided empirical evidence that SME managers undertake the most important decisions within their organisations (Van Gills, 2005), including those regarding innovation strategies, and their managerial perceptions shape the firm’s strategic behaviour to a significant degree (Alegrem et al, 2011; Donate and Sánchez de Pablo, 2015). In addition, several recent studies suggest that self-reported information by managers can be used as an adequate approach to measure business performance and other strategy variables, such as innovation (Foreman-Peck, 2013; Goya et al, 2016; Madrid-Guijarro et al, 2013; Ramanadi et al, 2017; Ribau et al, 2017). 3…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, several studies have provided empirical evidence that SME managers undertake the most important decisions within their organisations (Van Gills, 2005), including those regarding innovation strategies, and their managerial perceptions shape the firm’s strategic behaviour to a significant degree (Alegrem et al, 2011; Donate and Sánchez de Pablo, 2015). In addition, several recent studies suggest that self-reported information by managers can be used as an adequate approach to measure business performance and other strategy variables, such as innovation (Foreman-Peck, 2013; Goya et al, 2016; Madrid-Guijarro et al, 2013; Ramanadi et al, 2017; Ribau et al, 2017). 3…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, several studies have demonstrated empirical evidence that SME managers implement "the most important decisions within their organizations" (Van Gils 2005; Exposito and Sanchis-Llopis 2018), including those regarding innovation strategies and their managerial perceptions shape the firm's strategic behaviour to an essential degree Donate and Pablo 2015). Furthermore, several other studies suppose that self-reported information by managers can be used as an appropriate approach to measure business strategy variables including innovation and business performance (Foreman-Peck 2013; Goya et al 2016;Madrid-Guijarro et al 2013;Ramadani et al 2017;Ribau et al 2017;Exposito and Sanchis-Llopis 2018;Wang and Ahmed 2004) and financial slacks (Parida and Örtqvist 2015;Boso et al 2017).…”
Section: Data Collectionmentioning
confidence: 99%
“…Desde la publicación de Griliches (1979) se ha desarrollado un amplio cuerpo de literatura que examina la relación entre la innovación, la productividad y el crecimiento empresarial (Coad et al, 2016;Goya et al, 2016). Dentro de este ámbito, se incluyen las actividades de I+D, aunque hay que tener en cuenta, que la innovación trasciende a otros ámbitos, como mª isabel martínez martín, miguel sánchez galindo, césar pérez lópez y rosa santero sánchez las infraestructuras tecnológicas y las estrategias de cooperación entre empresas y otros agentes (Audretsch y Callejón, 2007;Segarra, 2014).…”
Section: Innovación En La Empresa Y Factores Moderadoresunclassified
“…En relación a los diferentes sectores de actividad, la evidencia empírica indica que el impacto de los gastos en innovación sobre la productividad es más fuerte en sectores de alta tecnología, aunque los efectos inter-industrias puede favorecer incluso a los sectores de bajo nivel tecnológico (Goya et al, 2016). En una agrupación de empresas en clústeres, Rodeiro y López (2007) encuentran que el clúster de empresas de tamaño mediano, innovadoras y eficientes, se encuentran principalmente en los sectores industriales y energéticos, mientras que el clúster de empresas pequeñas e innovadoras, tiene una mayor representación en sectores de servicios, de actividades inmobiliarias y empresariales, sectores que generalmente están vinculados con actividades de alto contenido tecnológico.…”
Section: Factores Moderadores Sobre El Desempeño Empresarialunclassified
See 1 more Smart Citation